Linear‐No‐Threshold Default Assumptions are Unwarranted for Cytotoxic Endpoints Independently Triggered by Ultrasensitive Molecular Switches. Issue 10 (24th April 2017) - Bogen, Kenneth T.
Abstract: Crump's response in this issue to my critique of linear‐no‐threshold (LNT) default assumptions for noncancer and nongenotoxic cancer risks ( Risk Analysis 2016; 36(3):589–604) is rebutted herein. Crump maintains that distinguishing between a low‐dose linear dose response and a threshold dose response on the basis of dose–response data is impossible even for endpoints involving increased cytotoxicity. My rebuttal relies on descriptions and specific illustrations of two well‐characterized ultrasensitive molecular switches that govern two key cytoprotective responses to cellular stress—heat shock response and antioxidant response element activation, respectively—each of which serve to suppress stress‐induced apoptotic cell death unless overwhelmed. Because detailed dose–response data for each endpoint is shown to be J‐ or inverted‐J‐shaped with high confidence, and because independent pathways can explain background rates of apoptosis, LNT assumptions for this cytotoxic endpoint are unwarranted, at least in some cases and perhaps generally.